2022
DOI: 10.3389/fgene.2022.879899
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: A Novel Homozygous Frameshift Mutation of the SKIV2L Gene in a Trichohepatoenteric Syndrome Patient Presenting With Short Stature, Premature Ovarian Failure, and Osteoporosis

Abstract: Background: Trichohepatoenteric syndrome (THES) is a rare Mendelian autosomal recessive genetic disease characterized by intractable diarrhea, woolly hair, facial abnormality, immune dysfunction, and intrauterine growth restriction. THES mutations are found in the TTC37 and SKIV2L genes, which encode two components of the human superkiller (SKI) complex.Methods and results: We report one case of a 32-year-old woman of Chinese descent with THES, who was born with a low weight (2000 g). She had intractable diarr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Moreover, SNP array analysis revealed an 11.7Mb LOH on 6p22.3p21.31 in foetus 6. 6p22.3p21.31 contains VARS2, SKIV2L, and 39 other genes related to autosomal recessive diseases [39,40]. Studies have reported clinical phenotypes including foetal developmental delays, hyperglycaemia, and dehydration [41].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, SNP array analysis revealed an 11.7Mb LOH on 6p22.3p21.31 in foetus 6. 6p22.3p21.31 contains VARS2, SKIV2L, and 39 other genes related to autosomal recessive diseases [39,40]. Studies have reported clinical phenotypes including foetal developmental delays, hyperglycaemia, and dehydration [41].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors expand this spectrum of clinical signs by two less frequent symptoms, that is, (8) congenital cardiac defects (particularly in the Asian population; Fabre et al, 2012, 2013, 2014, 2017; W. I. Lee et al, 2016); and (9) platelet abnormalities (Fabre et al, 2012, 2013, 2014, 2017; Hartley et al, 2010). Other anomalies detected in THES patients include: enteric symptoms (colitis, intestinal villous atrophy; abnormal sorting and/or decreased expression of several brush‐border transport proteins, such as: Na + /H + exchangers, aquaporin 7, Na + /I − symporter and the H + /K + ATPase, on the apical surface of jejunal enterocytes, was demonstrated by immunohistochemistry; Hartley et al, 2010), hypoglycemia (Gao et al, 2022; Xinias et al, 2018), dental abnormalities (Karaca Edeer et al, 2019), premature birth with low birth weight (Fabre et al, 2012; Fabre et al, 2013), short stature (below third percentile in 50% of individuals; Fabre et al, 2014; M. Yang, Jiang, et al, 2022), and mild mental retardation (Fabre et al, 2014). Due to such a wide spectrum of symptoms, the prognosis is poor and one of THES characteristics is high mortality rate (up to 50%)—many patients die before the age of 5–10 and just a few affected individuals survived up to the third decade (Fabre et al, 2014).…”
Section: Trichohepatoenteric Syndrome (Thes)—a Major Clinical Manifes...mentioning
confidence: 99%
“…Curiously though, theoretically less harmful mut 7 in the homozygous state was associated with later onset diarrhea and severe combined immunodeficiency in a patient, who additionally presented with Pneumocystis jirovicii pneumonia (PJP) and postnatally acquired CMV infection (Hosking et al, 2018). On the other hand, the female patient with homozygous mutation leading to production of the most severely truncated SKI2W among all cases studied (c.12_13 delAG, p.Glu5Ala fs*37; mut 1 ; Table 3 and Figure 11b), who suffered from mild diarrhea in the neonatal period, was able to survive until the age of >30 years, which allowed to observe novel symptoms, that is, premature menopause and osteoporosis (M. Yang, Jiang, et al, 2022). All these examples show that it is virtually impossible to capture any logical correlation between specific genotypes and phenotypes of THES patients.…”
Section: Trichohepatoenteric Syndrome (Thes)—a Major Clinical Manifes...mentioning
confidence: 99%